UPDATE THE DIVERSITY OF BIRDLIFE IN THE MUNICIPALITY OF BAGÉ, REGION CAMPAIGN, RIO GRANDE DO SUL, BRAZIL - Corrêa, Luiz Liberato Costa; Mello, Luciano Moura de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The present study aims to disseminate the current list of wild birds recorded for the city of Bagé, contributing information on the occurrence of this ornithological group in Region Campaign, Rio Grande do Sul. By compiling records and sampling efforts, it is recorded 172 species for the municipality and these six species are considered threatened at regional, what becomes extremely important studies conservation in this region.